Wide-field choroidal thickness profile in healthy eyes. Issue 1 (December 2018) - Rasheed, Mohammed; Singh, Sumit; Invernizzi, Alessandro; Cagini, Carlo; Goud, Abhilash; Sahoo, Niroj; Cozzi, Mariano; Lupidi, Marco; Chhablani, Jay
Abstract The introduction of wide field optical coherence tomography (WF-OCT) has provided newer insights in the imaging of peripheral choroid. We evaluated choroidal thickness (CT) and large choroidal vessel thickness (LCVT) of 20 eyes in horizontal and vertical meridians using WF-OCT. A high-definition line scan through the fovea in both horizontal and vertical meridian was captured in primary and extremes of gaze to obtain scans up to mid-equator. CT and LCVT measurements were done across predefined points in macular area and all quadrants. LCVT was calculated after identifying a large choroidal vessel near choroidoscleral interface. The main outcome measures were differences in CT and LCVT in macular and four quadrants. Mean CT (331.23 ± 76.34 µ) and LCVT (201.46 ± 54.31 µ) in vertical macular segment were significantly more than CT (245.79 ± 55.38 µ; p = 0.0002) and LCVT (150.48 ± 52.58 µ; p = 0.004) in horizontal macular segment. CT at peripheral points in all quadrants was significantly reduced as compared to subfoveal CT (all p values < 0.05) with maximum reduction in inferior quadrant (64.5%). Using linear regression, only quadrant had a significant effect on CT and LCVT (both p < 0.001). CT and LCVT are highest at the macular area with reduction towards the periphery. The contribution of LCVT to CT is less at the fovea compared to other peripheral points.